2003
DOI: 10.1577/t02-092
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Assessment of Strain-Specific Sources of Lake Trout Recruitment in the Great Lakes

Abstract: Populations of wild lake trout Salvelinus namaycush have been extirpated from nearly all their historical habitats across the Great Lakes. Efforts to restore self-sustaining lake trout populations in U.S. waters have emphasized the stocking of coded-wire-tagged juveniles from six hatchery strains (Seneca Lake, Lewis Lake, Green Lake, Apostle Islands, Isle Royale, and Marquette) into vacant habitats. Strain-specific stocking success has historically been based on estimates of the survival and catch rates of cod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(52 citation statements)
references
References 65 publications
2
50
0
Order By: Relevance
“…The SMD and Isle Royale (SIW) strains were selected as the low F st case (F st [ 0.01). Details on hatchery strains may be found in Page et al (2003). Spawning of adults were conducted by U.S.…”
Section: Empirical Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…The SMD and Isle Royale (SIW) strains were selected as the low F st case (F st [ 0.01). Details on hatchery strains may be found in Page et al (2003). Spawning of adults were conducted by U.S.…”
Section: Empirical Samplesmentioning
confidence: 99%
“…We then summarized results characterizing the importance of gene correlations and apportionment of genetic variation on assignment error rate. We estimated accuracy of individual strain classification using multilocus genotype frequencies of each lake trout broodstock as described previously (Page, 2001;Page et al, 2003) using the leave-one-out procedure (Efron, 1983). We assigned progeny from low coancestry and high coancestry groups of unknowns for each inter-strain comparison to determine whether accuracy of individual assignments was random across samples.…”
Section: Assignment Testsmentioning
confidence: 99%
“…A previous genetic study of lake trout from Lake Huron showed that these three strains accounted for the majority of wild lake trout captured (Page et al 2003). In addition, these strains accounted for the majority (N80%) of the stocking in the areas were sampled and tagging data indicated that most lake trout stocked into northern Lake Huron remained in that area (Madenjian et al 2004).…”
Section: Geneticsmentioning
confidence: 99%
“…Since their introduction into Lake Huron, Senecastrain lake trout made up the majority of spawners found in the Drummond Island Refuge and on Six Fathom Bank between 1991 and 1995 even though equal numbers of each strain were stocked (Table 1). In the Drummond Island Refuge, Seneca-strain lake trout made up nearly 100% of spawning sized lake trout captured between 1991 and 1995; on Six Fathom Bank, over half of the spawning-sized lake trout captured were of the Seneca strain (Page et al 2003).…”
Section: Genetics-assignment Testsmentioning
confidence: 99%
See 1 more Smart Citation